Identification of preferred combination of factors in manufacturing bioepoxy/clay nanocomposites - Salam, H.; Dong, Yu; Davies, I.; Pramanik, Alokesh (2018)
The current study aims to identify the preferred combination of factors for manufacturing bioepoxy/clay nanocomposites based on epoxidised soybean oil (ESO), including material formulation and manufacturing parameters for maximising tensile strengths of nanocomposites according to Taguchi design of experiments (DoEs). A Taguchi mixed-level DoEs with an L16 orthogonal array was selected. The response was set to achieve the maximum tensile strengths of nanocomposites with a preferred combination of factors determined by the Pareto analysis of variance (ANOVA). The associated results revealed that the ESO content was found to be the most significant factor with a contribution percentage of 66.63% amongst nine factors investigated. This result was followed by two less significant factors, namely mechanical mixing speed and clay content with contribution percentages of 19.09 and 7.01%, respectively. However, other factors of clay type, curing agent type, mechanical mixing temperature and time, as well as sonication frequency and time, were categorised as non-significant factors from the manufacturing and economical point of view. A confirmation test was conducted based on the preferred combination of factors showing good agreement with statistically predicted results.